(untitled) (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article analyzes the impact of the 2022–2023 energy crisis on the economies of Central Asian countries, with particular focus on Kazakhstan over the period 2019–2024. The study is based on an assessment of global energy price dynamics and key macroeconomic indicators characterizing economic security. The paper employs descriptive and comparative macroeconomic analysis, distinguishing the pre-crisis period, the peak stages of the crisis, and the adaptation phase. Using data from the World Bank and the U.S. Energy Information Administration, the main changes in economic growth rates, inflation levels, and exchange rate fluctuations are identified. The results demonstrate that the energy crisis exerted a dual impact, combining increased export revenues with significant domestic macroeconomic risks. General conclusions are drawn regarding the nature of the energy crisis’s effect on the economies of Central Asian countries.